CONSTITUTIONAL COURT OF BOSNIA AND HERZEGOVINA – BETWEEN HYBRIDITY AND POWER SHARING - Barbarić, Dražen (Politeia, 2025)
The aim of the paper is to analyze the role and function of the Constitutional Court of Bosnia and Herzegovina through the lens of two political concepts that are much more represented in the analysis of political than judicial institutions. It is about the concept of ’hybrid courts’ and the concept of ’power sharing courts’. The first concept refers to those courts that enable or require the presence of foreign judges in domestic judicial institutions, in this case the Constitutional Court of Bosnia and Herzegovina. Since its founding, the latter has included three foreign judges in its composition, and over time, the perception of their work and role has changed dramatically, maintaining broader trends that exist in the political sphere of BiH. The paper will analyze this moment of hybridity of the Constitutional Court of BiH and the repercussions that this feature had when making decisions. The second concept refers to a certain consociational element that the Constitutional Court has in its structure, namely, its composition reflects the reciprocity of the constituent peoples as a kind of guarantor that the established Dayton order will not be changed unilaterally or by force without the consent of all three constituent peoples. The phenomenon of power sharing within the Court and the repercussions it brought about in the function of the Court itself will be presented in detail. Only by analyzing these two crucial elements is it possible to fully understand the functioning of the Constitutional Court, the problems it faces during its work, and the discussions it provokes in the political and academic spheres. Precisely through these two elements, it is possible to plausibly show that the Constitutional Court of Bosnia and Herzegovina is between the hammer and the anvil. On the one hand, it is expected to have transformational potential and to modify the Dayton constitutional legal framework, and on the other hand, it serves as a mechanism for maintaining and preserving the latter.